Mixed Tukey EWMA-CUSUM control chart and its applications. Issue 4 (2nd October 2017) - Riaz, Muhammad; Khaliq, Qurat-Ul-Ain; Gul, Shahla
Abstract: Tukey control chart (TCC) is a popular choice for robust monitoring of process parameters. With the advancement in technology, we develop refined techniques that incorporate multiple aspects in a single structure. This article is a similar effort to design an improved charting structure in the form of mixed Tukey EWMA-CUSUM chart (namely MEC-TCC). We have investigated the performance of the proposed chart using different run length properties. We have observed that the proposed MEC-TCC design serves the dual objectives, namely the efficient detection of shifts and robustness against non-normality. The comparative analysis has revealed that the proposed scheme is an effective competitor to the existing counterparts, including classical Shewhart, EWMA, CUSUM, Tukey and some other variants such as mixed EWMA-CUSUM, Tukey EWMA, Tukey CUSUM. Moreover, the proposed design presents some of the aforementioned charts as special cases. For real life considerations, we have implemented the proposed and existing charts to two real life data sets, one related to air quality and the other one concerning smartphone accelerometer.